2015
DOI: 10.1111/mmi.13241
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of three topoisomerases that regulate DNA supercoiling levels in Chlamydia

Abstract: Summary Chlamydia is a medically important bacterium that infects eukaryotic cells. Temporal expression of chlamydial genes during the intracellular infection is proposed to be regulated by changes in DNA supercoiling levels. To understand how chlamydial supercoiling levels are regulated, we purified and analyzed three putative Chlamydia trachomatis topoisomerases. As predicted by sequence homology, CT189/190 are the two subunits of DNA gyrase, whereas CT643 is a topoisomerase I. CT660/661 have been predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 58 publications
0
20
1
Order By: Relevance
“…However, the increased relaxation has a weak negative influence on the S. coelicolor topA gene, i.e., the overproduction of TopA slightly inhibits both p1 and p2 activities. Such regulation is remarkably different from the efficient negative-feedback mechanism of topA expression that has been described for other bacterial species ( 18 , 19 , 46 , 49 ). In the closely related species M. smegmatis and M. tuberculosis , topA transcription (also controlled by two promoters) is very efficiently inhibited by chromosomal relaxation induced by novobiocin treatment or TopA overproduction ( 19 ).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…However, the increased relaxation has a weak negative influence on the S. coelicolor topA gene, i.e., the overproduction of TopA slightly inhibits both p1 and p2 activities. Such regulation is remarkably different from the efficient negative-feedback mechanism of topA expression that has been described for other bacterial species ( 18 , 19 , 46 , 49 ). In the closely related species M. smegmatis and M. tuberculosis , topA transcription (also controlled by two promoters) is very efficiently inhibited by chromosomal relaxation induced by novobiocin treatment or TopA overproduction ( 19 ).…”
Section: Discussioncontrasting
confidence: 66%
“…It has been demonstrated that supercoiling conditions affect both topA and gyrase gene transcription in a number of bacterial species ( 11 , 30 , 46 , 49 ), thereby providing a mechanism for maintaining topological balance. We expected that an elevated TopA level should be correlated with decreased gyrase gene transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During this stage of the developmental cycle, when RB-to-EB conversion is occurring, global gene expression profiling supports the hypothesis that about 20% of the genome is upregulated ( 33 , 34 ). Expression of many of these genes has been shown to be regulated by σ 66 , with additional factors, such as DNA topology and supercoiling, expected to contribute to this differential expression mechanism ( 35 37 ). σ 28 has been shown to regulate few (but critical) genes during the RB-to-EB conversion process, including those involved in the formation of the condensed DNA structure that is unique to EBs ( 38 42 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, early genes are transcribed within the first few hours of EB entry into the host cell (Belland et al, 2003; Hayward et al, 2021; Humphrys et al, 2013). Midcycle genes are transcribed during RB replication and are proposed to be regulated by changes in chlamydial DNA supercoiling (Niehus et al, 2008; Orillard and Tan, 2015). Late genes are transcribed at the time of RB-to-EB conversion and are regulated by a transcription factor EUO (Rosario et al, 2014; Rosario and Tan, 2012).…”
Section: Introductionmentioning
confidence: 99%